THE ACT OF READING THOREAU’S WALDEN - Salles, Ana Lúcia Almeida (Em Tese, 2004)
This essay investigates Henry David Thoreau’s Walden from the perspective of Wolfgang Iser’s theory of reader-response. The present analysis demonstrates the presence of negations and blanks, and detects strategies that leadthe reader to respond by assembling meanings, constructing images, identifying metaphors, and participating in some of the narrator’s transcendental experiences.